PENGARUH WAKTU PEMETIKAN TERHADAP KADAR FLAVONOID TOTAL DAN AKTIVITAS ANTIOKSIDAN ESKTRAK DAUN KELOR (Moringa oleifera) - Aulianshah, vonna; Rasidah, Rasidah; Handayani, Rini (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
Moringa is a plant that is believed to have antioxidant activity that is able to provide cell defense against reactive oxygen species that cause cell damage. This activity is likely mediated by the high total flavonoid content of Moringa leaves, but the chemical content of the plant is highly dependent on several factors, one of which is the time of picking or picking. The purpose of this study is to determine the effect of picking time on the total level of flavonoids and antioxidant activity of Moringa leaf extract (Moringa oleifera). The study was experimental by using two bound variables, namely total flavonoid levels and antioxidant activity from moringa leaf extract collected with different picking, namely at 6-7 a.m (EEDK1), 12-13 p.m (EEDK2) and 17-18 p.m (EEDK3) on the same day. Moringa leaf extract is made using a repetitive maceration method with a 70% ethanol solvent. The measurement of total flavonoid levels was carried out by spectrophotometry method with a concentration of 10,000 ppm and used quercetin as the benchmark standard. Antioxidant activity was determined through the DPPH method with extract concentrations of 20, 40, 60, 80 and 100 ppm. The measurement results were analyzed for the percentage of inhibition and the IC50 (inhibitory concentration) value was calculated using the linear regression curve equation. Vitamin C was used as a comparison The measurement results of each test sample showed a significant difference in the percentage of inhibition and IC50 value, where EEDK1 was the most active and categorized as very strong with a value of 45.08 ppm. With these significant differences, it can be concluded that the picking time affects the total flavonoid levels and anti-oxidation activity of Moringa leaves